2016
DOI: 10.1073/pnas.1609934113
|View full text |Cite
|
Sign up to set email alerts
|

FASN regulates cellular response to genotoxic treatments by increasing PARP-1 expression and DNA repair activity via NF-κB and SP1

Abstract: Fatty acid synthase (FASN), the sole cytosolic mammalian enzyme for de novo lipid synthesis, is crucial for cancer cell survival and associates with poor prognosis. FASN overexpression has been found to cause resistance to genotoxic insults. Here we tested the hypothesis that FASN regulates DNA repair to facilitate survival against genotoxic insults and found that FASN suppresses NF-κB but increases specificity protein 1 (SP1) expression. NF-κB and SP1 bind to a composite element in the poly(ADP-ribose) polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 55 publications
(47 reference statements)
1
76
0
Order By: Relevance
“…Recently, therapies targeting AR have been shown to be effective in SDC patients and have attracted attention [32]. The overexpression of FASN was reported to be linked to castration-resistant prostate cancer growth and resistance to chemotherapy [24,33]. Future studies are expected to clarify the association between these therapies and the FASN expression in SDC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, therapies targeting AR have been shown to be effective in SDC patients and have attracted attention [32]. The overexpression of FASN was reported to be linked to castration-resistant prostate cancer growth and resistance to chemotherapy [24,33]. Future studies are expected to clarify the association between these therapies and the FASN expression in SDC.…”
Section: Discussionmentioning
confidence: 99%
“…However, PARP1 may mediate 14-3-3σ regulation of Chk2 expression. Recently, we have shown that the PARP1 gene promoter contains a NF-κB-binding element and that NF-κB negatively regulates PARP1 expression in another cell line, Panc-1 (20). It has also been shown that 14-3-3 proteins could bind to both p65 and IκBα and facilitate the nuclear export of IκBα-p65 complexes (44).…”
Section: Discussionmentioning
confidence: 99%
“…The host cell reactivation-based NHEJ assay was performed as previously described with modifications (20). Briefly, 5×10 4 cells/well were seeded in 24-well plates and cultured for 24 hrs before transfection with either linearized or intact pGL3-Luc plasmid with firefly luciferase reporter gene (400 ng/well) using Metafectene Pro.…”
Section: Methodsmentioning
confidence: 99%
“…This observation may have translational implications, since olaparib, rucaparib, and niraparib were recently approved by the FDA as maintenance therapy in platinum-sensitive patients, regard- PARP-1 expression may also play a role in predicting inherent or incurred DNA damage burden to identify DNA repair deficiencies or even treatment response as a functional biomarker of HRD (44,45). We are currently entering several clinical trials in both breast and ovarian cancer at the University of Pennsylvania to directly evaluate [ …”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%